DINAMIKA PERTUMBUHAN PENDUDUK DAN KEJADIAN BANJIR DI KOTA: KASUS SURABAYA - Luh Kitty Katherina (Research Centre for Population, Indonesian Institute of Sciences, 2017)
This paper aims to identify the relationship between population growth and disaster incidents, especially flood in the city. Surabaya was chosen as a study area because of its large population and regular flooding incidents. The analysis is done by using secondary data, namely number of population as well as disaster incidents. The method used is quantitative descriptive analysis with correlation test, by using data of population growth rate and density, as well as data of flooding incidents. The study shows that population growth has a significant relationship with the number of flood events. Besides that, there is a tendency of sub-districts with high growth rate also have the highest number of flooding incidents. However, sub-districts with low growth rate with dense population also have high flood incidents. A large number of population is one of the triggers for the increase of disaster occurrence. It is because the high population growth in the limited urban land encourages residents to live in disaster-prone areas and the occurrence of inappropriate land conversion’s allocation. The reducing of water absorbent areas affects the runoff and the water discharge that enter the city, particularly when the rainy season arrives